Fortress of the Stone Dragon - West, Tracey, 1965-; Loveridge, Matt (2020)
Not all of the wizards who were freed from Maldred's time-trap were good wizards; one of them, Astrid, is planning on working a spell that will bring to life the bones that lie scattered in the Fortress of the Stone Dragon, bones that belonged to creatures much bigger than dragons--and when his friends are turned to stone it is up to Drake to find a way to save them, including his own dragon, Worm.
Grade 2.
Ages 6-8.
Grades 1-3.
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Adventure stories; Dragons -- Fiction; Magic -- Fiction; Wizards -- Fiction; Adventure and adventurers -- Fiction; Action and adventure fiction